Analgesic monoterpene indole alkaloids from Gelsemium elegans stems - Pengfei JIN; Guijuan ZHENG; Lang HUANG; Xinghua YUAN; Xiaomin MA; Guanqun ZHAN; Adila ABUDUREXITI; Guangmin YAO (Journal of Holistic Integrative Pharmacy)
Objective: The aim of this study is to search for potent analgesics from the stems of Gelsemium elegans. Methods: Alkaloids were isolated from the samples of G. elegans and purified using column chromatograph and High-Performance Liquid Chromatography. The chemical structures of the isolated alkaloids were determined using extensive high resolution electrospray ionization mass spectroscopy (HRESIMS) and nuclear magnetic resonance (NMR) spectroscopic data analyses, 13C NMR DP4+ analysis and electronic circular dichroism (ECD) calculations, and Rh2(OCOCF3)4-induced ECD data analysis. The analgesic activities of all the isolates were analyzed using an acetic acid-induced writhing test in mice. Results: Two new monoterpene indole alkaloids, elegansine A (1) and 14-hydroxysempervirine (2), and seven known monoterpene indole alkaloids were isolated from the stems of G. elegans. Elegansine A (1) represents the first example of sarpagine-type alkaloids with a Δ15(20) double bond. All the alkaloids (1–9) showed potential analgesic activities. Three alkaloids, namely 14-hydroxysempervirine (2), 14β,20α-dihydroxydihydrorankinidine (4), and 14-hydroxygelsenicine (6), exhibited significant analgesic activities in the acetic acid-induced writhing test in mice at a dose of 5.0 mg/kg with the writhing inhibition rates of 69.5%, 69.2%, and 72.7%, respectively. Conclusion: These results enlarged the diversity of monoterpene indole alkaloids and also provided a new basis to develop novel potent analgesics.